Legal Analysis of the Impact of Unregistered Marriage on Voter Data in Palu City - Megawati, Megawati; Nurkhaerah, Sitti; Markarma, Andi (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
The aim of the study is to describe sirri marriage as one of the factors in the problems that occur in voter data and the implications of the impact of sirri marriage on voter data in Palu City. The issues raised are how the implications of the impact of sirri marriages on voter data in Palu City and how the legal analysis of the results of sirri marriages on voter data in Palu City. The research method used is qualitative method and the data was gathered through field observation, in-depth interview, and documentation. The methodologyy was reinforced by the Maqashid Asy-Syariah approach. The results of the study indicate that sirri marriage is one of the problems with voter data, namely in the process of updating voter data. The impact is that it has a negative impact on the election process, namely the loss of voting rights, the occurrence of multiple voter list problems, and for children if there is no data recording, they also cannot be registered on the voter list. With the Minister of Home Affairs No. 8 of 2019, children from sirri marriages can record their identities, it's just that many other children's rights will be lost, it is better for the perpetrators of this sirri marriage and their children to be advised to do isbat marriage so that their marriage is recorded.